STRENGTHENING RESILIENCE IN CHILDRENS PSYCHOLOGICAL DISORDERS OF ABDULLAH NASHIH ULWANS PERSPECTIVE - Muh. Haris Zubaidillah; M. Ahim Sulthan Nuruddaroini (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2021)
Psychological disorders in children such as insecurity, timidity, low self-esteem, feelings of anxiety, and desires need solutions and antidotes. This study aims to describe the antidote for psychological disorders through the concept of Abdullah Nashih 'Ulwan. This study uses the library research method, data collection techniques use documentation techniques, while data analysis techniques use content analysis. The results of this study state that Abdullah Nashih 'Ulwan's concept of psychological education in his essay entitled Tarbiyatul Aulad Fi Al-Islam, revealed that there are four factors of psychological problems or disorders in a child that must be prevented and even treated by educators. The four factors are inferiority insecurity, afraid, feelings of having flaws, and envy. Abdullah Nashih 'Ulwan also explained the concept of a bidder for these four factors as described in the explanation in this article. Theoretically, practical and empirical research is expected to provide benefits for teachers and parents in strengthening resilience to children's psychological disorders by using the concept of Abdullah Nashih 'Ulwan's psychological education.